2009
DOI: 10.1038/nphys1482
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale non-equilibrium dynamics and the fluctuation–dissipation relation in an ageing polymer glass

Abstract: Response functions 1 and fluctuations 2 measured locally in complex materials should equally well characterize mesoscopic-scale dynamics. The fluctuation-dissipation relation (FDR) relates the two in equilibrium, a fact used regularly, for example, to infer mechanical properties of soft matter from the fluctuations in light scattering 3 . In slowly evolving non-equilibrium systems, such as ageing spin 4,5 and structural glasses 6,7 , sheared soft matter 8 and active matter 9 , a form of FDR has been proposed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…Notice that position dependence of the v's and of the α's is a necessary but not sufficient condition for the existence of stationary solutions. Further, the relations (7) and (8) lead to a mapping between the stationary solutions of run-and-tumble particles and the corresponding stationary distributions of a drift-diffusion equation of Brownian motion in inhomogeneous media, analogously to the one presented in Ref. [28].…”
Section: B Trapped Active Motion: Stationary Solutionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Notice that position dependence of the v's and of the α's is a necessary but not sufficient condition for the existence of stationary solutions. Further, the relations (7) and (8) lead to a mapping between the stationary solutions of run-and-tumble particles and the corresponding stationary distributions of a drift-diffusion equation of Brownian motion in inhomogeneous media, analogously to the one presented in Ref. [28].…”
Section: B Trapped Active Motion: Stationary Solutionsmentioning
confidence: 90%
“…Notwithstanding this, today there has been great effort made to give a thermodynamic description of active matter [5,6]. On this course, the concept of effective temperature T eff is valuable and has been explored theoretically and experimentally in a variety of systems in nonequilibrium situations [7][8][9][10][11][12][13][14][15][16][17][18], particularly in the dilute regime [19]. More recently, it has been shown that the effective temperature in a two-component active Janus particles can be considered a control parameter (in the sense of a thermodynamics variable) for the observed kinetics and * fjsevilla@fisica.unam.mx; phase behavior [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is also potential for applications in experiments: attractions between colloidal particles can now be manipulated in real-time, 23,[43][44][45][46][47][48] and correlation-response measurements have also been made. [49][50][51] We hope that the potential for automated self-assembly using real-time feedback will stimulate further studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…First, L was matched only to t w (irrespectively of the probing time t + t w ). Second, our SDD matched spatial correlation functions whose experimental study is only incipient [9,10].One could think [5] of building an SDD through the Generalized Fluctuation Dissipation relations (GFDR) first introduced in [11] (for related developments see [12][13][14][15][16][17][18][19]). The GFDR are correct at very large times.…”
mentioning
confidence: 99%
“…One encounters numerical studies for both Ising [13,16,18] and Heisenberg [21,22] spin glasses, as well as for structural glasses [23][24][25][26][27]. On the experimental side, we have studies on atomic spin glasses [17,19], superspin glasses [10], polymers [9,28], colloids [29][30][31][32][33][34][35] or DNA [36].Here, we perform a detailed simulation of GFDR in the three-dimensional Ising spin glass employing the custommade supercomputers Janus [37] and Janus II [38]. In fact, this has been the launching simulation campaign of the Janus II machine, which was designed with this sort of dynamical studies in mind.…”
mentioning
confidence: 99%